(untitled) (Research, Society and Development, 2022)
Molar incisor hypomineralization (MIH) consists of a change in the structure of dental enamel caused by environmental factors that can influence the period of enamel calcification, altering its quality. The treatment options for the consequences of hypomineralization range from preventive procedures, such as topical application of fluoride and fluoride varnishes, through conservative or invasive restoration procedures, with or without tooth preparation, to the extraction of affected teeth. The objective of this study is to report the clinical case of an 8-year-old child with MIH, affecting the upper and lower incisors with complaints of sensitivity and aesthetic impairment. The treatment included microabrasion and, later, the making of composite resin restorations. The approach adopted resulted in a reduction in sensitivity, measured with the application of an air jet, and improved esthetics reported by the patient. It is concluded that the conservative treatment of composite resin associated with microabrasion was effective in improving the clinical appearance of incisor opacities in children.